Ab initio modeling of defects in silicon, germanium and SiGe alloys - Torres, V. J. B. (2005)
Understanding the most elemental defects in semiconductors is a fundamental step to grasp the countless solid-state reactions that may occur during crystal growth, device processing and operation stages. The higher carrier mobilitity in SiGe alloys and germanium, when compared with silicon, and the necessity to a higher K dielectric than SiO2 makes these semiconductors the most contendors to a new generation of electronic devices. Our aim is to model self and impurity point defects in SiGe alloys and germanium, and compare with their equivalent complexes in silicon. We use density functional theory and pseudopotentials to determine the structural, electronic and vibrational properties. The calculations are performed in a 32 CPU PC cluster, in Physics Department of Aveiro University.